An Institutional Internet Laboratory: The Croatian Database on Antiquity - Gračanin, Hrvoje (Array, 2005)
The paper deals with the work of the Internet Laboratory at the Faculty of Philosophy, Department of History, Zagreb University. Special emphasis is put on the support provided by Laboratory to two IT research projects Eurykleia - Written Sourcers from Antiquity for the Ancient History of the Croatian Historical Area I: Main Geographic Sources, and Croato-Aegyptica electronica - Database of the Egyptian Monuments in the Museum and Private Collections in Croatia.